Implementasi Ibadah Shalat Melalui Mata Pelajaran Al-Islam Pada Siswa SMA Muhammadiyah 1 Bandar Lampung - Hidayatullah; Ahmad Luviadi; Arizal Eka Putra (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2025)
This study aims to analyze the effectiveness of Al-Islam learning in enhancing students' understanding of prayer (shalat) at SMA Muhammadiyah 1 Bandar Lampung. Observations revealed that students' comprehension of prayer remains theoretical and is not fully applied in daily life. Many students memorize prayers without understanding their meaning and lack consistency in performing shalat, especially outside school hours. Factors such as technology influence, social environment, heavy academic workload, and less engaging teaching methods pose challenges in raising students' awareness of the importance of prayer. To address these issues, the school has implemented an integrative learning method combining theory and direct practice. This approach includes utilizing the school mosque as a learning center, fostering a culture of mutual encouragement among students, and providing continuous motivation and guidance from the school. Additionally, the integration of educational technology, standardized prayer teaching methods, and academic schedule adjustments are key strategies to ensure that students not only understand prayer theoretically but also practice it with full awareness and sincerity. Through this approach, it is expected that students' spiritual character will be better developed, enabling them to make shalat an inseparable part of their lives.